Otimização topológica aplicada a sistema de elevação de carga - Cruz, Vinícius de Jesus Berci da (2022)
The optimization of mechanical elements such as lifting hooks has become recurrent nowadays. The improvement on engineering software’s as Computer aided design (CAD) and structural simulation enable a better efficiency in these studies. The objective of the study is to use tools such as the Finite Element Method and topological optimization to change the standard hook weight while maintaining its mechanical properties, thus saving energy and feedstock. The methodology of the study starts from the CAD modeling of a lifting hook according to NBR 10070, this standard model will be the basis of comparison for the optimized models. Along with NBR 10070, NBR 8400 parts 1, 2 and 3 will serve as the basis for defining the hook lifting load, fixing conditions, mechanical properties, and all other necessary requirements. After modeling, the ANSYS software will be used to obtain information such as stress values for static failure, life expectancy of hook fatigue and to perform the topological optimization itself. 3 elements were generated, the norm standard, optimized by ANSYS and a new modeling. The final element showed a mass reduction of 38.22% with a safety factor of 6.5.